Schools of quality : an introduction to total quality management in education - Bonstingl, John Jay. (California : Corwin press, 2001)
Successful schools are built on a strong foundation of Quality. In this book, Bonstingl outlines the blueprints for creating such a foundation and provides practical tools and examples for putting the Quality Philosophy to work at every level
Includes bibliographical references.
Keywords: School management and organization -- United States; Total quality management -- United States; Education -- United States -- Philosophy